2001
DOI: 10.1002/ar.1116
|View full text |Cite
|
Sign up to set email alerts
|

Tissue engineering in the cardiovascular system: Progress toward a tissue engineered heart

Abstract: Achieving the lofty goal of developing a tissue engineered heart will likely rely on progress in engineering the various components: blood vessels, heart valves, and cardiac muscle. Advances in tissue engineered vascular grafts have shown the most progress to date. Research in tissue-engineered vascular grafts has focused on improving scaffold design, including mechanical properties and bioactivity; genetically engineering cells to improve graft performance; and optimizing tissue formation through in vitro mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 37 publications
0
39
0
Order By: Relevance
“…Despite a variety of prior strategies to tissue engineer elastin-rich constructs, [27][28][29][30] poor tropoelastin mRNA expression by adult cells have severely limited positive outcomes. 31,32 As mentioned in the Introduction, our ongoing study of HA cues for elastin regeneration is driven by prior work that suggested that several GAG types (HA, heparin sulfate) have roles in elastin synthesis, maturation, and organization in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a variety of prior strategies to tissue engineer elastin-rich constructs, [27][28][29][30] poor tropoelastin mRNA expression by adult cells have severely limited positive outcomes. 31,32 As mentioned in the Introduction, our ongoing study of HA cues for elastin regeneration is driven by prior work that suggested that several GAG types (HA, heparin sulfate) have roles in elastin synthesis, maturation, and organization in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Although groups have successfully fabricated membrane-like tisties limit cell growth (34). In addition, it is inherently difficult to correlate two-dimensional experiments to sues, such as heart valves (19), arteries (24), and skin (1), larger artificial tissues have been difficult to realize.…”
Section: Introductionmentioning
confidence: 99%
“…Several different approaches in cell transplantation and cardiac tissue engineering have emerged as potential treatments to restore cardiac function. 1 Implantation of skeletal muscle cells, bone marrow cells, mesenchymal stem cells, or myoblasts has been reported to stimulate revascularization of ischemic heart tissue and enhance cardiac function. 2,3 In addition, cell-seeded grafts have been proposed for in vitro cardiac tissue growth and subsequent in vivo transplantation.…”
mentioning
confidence: 99%